PENGARUH PENANGGULANGAN PENYAKIT CACINGAN TERHADAP STATUS GIZI DAN DAYA TERIMA PELAJARAN MURID SEKOLAH DASAR - Tjetjep Syarif Hidayat; Hermina Hermina; Erna Luciasari; Adhi Dharmawan Tato; Djoko Susanto (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
Infestation of worms is stiil considered as one of major public health problem in Indonesia especially among young school-age children. When the duration of inferestation takes relatively long time it might provide bad influence to nutritional status, physical and intellectual development and school performance of young children. The aim of the study is mainly stressed on collecting information of the influence of deworming control program to nutritional status and performance of learning acceptance among the Elementary School of grades 3, 4, and 5. Deworming control program consists of distribution of deworming pills twice a year and extention education specially stressed on the problem of infestation of worms. Out of 223 children of two Elementary Schools 166 children were covered in the study. The study showed that: there was a the trend of betterment among the experimental group with regard to prevalence of worm infestation, nutritional status, school attendance and achievment of learning acceptance compared to the control group. Due to relatively bad environment sanitation it is suggested to include program to intervene the environment sanitation in such that reinfection of worm infestation can be limited.Keywords: helminthiasis, learning achievment, nutritional status.